2022
DOI: 10.1111/1754-9485.13425
|View full text |Cite
|
Sign up to set email alerts
|

Failure to attend radiation oncology appointments during COVID‐19: Analysis of data from an Australian public hospital

Abstract: Introduction COVID‐19 has impacted lives worldwide. Public health guidance has advocated for minimisation of infection risk by encouraging social isolation and physical distancing. In response, many health services have changed delivery practices to increased use of telehealth. We undertook an audit of hospital attendance data collected from a radiation oncology service in a large public hospital in Victoria, Australia between January and September in 2019, and the same period in 2020. The aim was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…When reviewing the monthly percentage of non‐attendance during the study period, the rise identified from January 2020 could be at least partially attributed to the COVID‐19 pandemic, as seen in other health settings across the country 14 . The authors acknowledge that the issue of non‐attendance of clinic appointments is not exclusive to dermatology or even to regional and rural health services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When reviewing the monthly percentage of non‐attendance during the study period, the rise identified from January 2020 could be at least partially attributed to the COVID‐19 pandemic, as seen in other health settings across the country 14 . The authors acknowledge that the issue of non‐attendance of clinic appointments is not exclusive to dermatology or even to regional and rural health services.…”
Section: Discussionmentioning
confidence: 99%
“…When reviewing the monthly percentage of nonattendance during the study period, the rise identified from January 2020 could be at least attributed to the COVID-19 pandemic, as seen in other health settings across the country. 14 The authors acknowledge that the issue of non-attendance of clinic appointments is not exclusive to dermatology or even to regional and rural health services. Moreover, the authors also acknowledge that the reasons behind patients not attending their clinic appointments can be multifactorial and can range from simple human factors (e.g.…”
Section: Discussionmentioning
confidence: 99%